PERSEPSI PASIEN TERHADAP PELAKSANAAN DISCHARGE PLANNING DENGAN POTENSI RAWAT LANJUT DI RUANG DARUSALAM 5 RS AL ISLAM BANDUNG - Puteri, Deviany Eka; Susilaningsih, Francisca Sri; Marlianti Lumbantobing, Valentina Belinda (Journal Nursing Care and Biomolecular, 2017)
Discharge planning for hospitalized patient where nurses role is not limited to only routine actvities, which is re-control information only. Discharge planning is a form of nurseattitude in nursing services. It is often found where discharge planning execution was only given when patient is about to leave the hospital and nurses role in implementing dischargeplanning is not optimal. The aim of this study is to find out patients perception toward discharge planning execution in Room Darusalam 5 Al Islam Bandung Hospital. This study isa descriptive study using consecutive sampling technique. The sample of this study were inpatients in Room Darusalam 5 Al Islam Hospital consist of 50 inpatients, the average ofpatient going home each day is 2-3 patients. The result of this study shows that patients perception toward discharge planning execution overall is 54% positive, however, there are still discharge planning execution lacking according to its components which are communication support fulfillment and education info fulfillment which has 58% patients perception as less positive. Therefore, strategy development in implementing discharge planning is needed.